Effect of Work Motivation on Job Satisfaction in Telecommunication Sector of Pakistan-A Case Study of Pakistan Telecommunication Company Limited (PTCL) - Hussain, Rai Imtiaz; Usman, Sabookh; Sarmad, Saleh Muhammad; Haq, Ihsan Ul (International Journal of Asian Social Science, 2012)
Purpose/objective: The main objective of this study is to determine the relationship between the work motivation and job satisfaction. We will determine how work motivation effects job satisfaction.Methodology: Questionnaire methodology was applied through the conduct of survey from four districts of Pakistan. These districts were Okara, Sahiwal, Kasur and Pakpattan. PTCL offices operating in these districts were taken as sample to generate results. Data was collected in March and April 2012 from these offices. 100 questionnaires were distributed in these exchanges offices and 80 questionnaires were collected. These questionnaires were analyzed and tested by the use of SPSS and standard deviation, mean, correlation and regression analyses were applied to find out the results.Results and Findings: Work motivation had significant effect on the job satisfaction in PTCL and their relationship is positive. In this model, 50% of change in job satisfaction is due to work motivation. ValueOriginality: The study is helpful for the organization in distributing work to employees. Through our study organizations will determine the effect of work motivation on job satisfaction of employees.